2014
DOI: 10.1309/ajcp8h2vbdsciobf
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative GATA-3 Immunoreactivity in Breast, Bladder, Gynecologic Tract, and Other Cytokeratin 7–Positive Carcinomas

Abstract: Strong GATA-3 expression is a reliable marker of primary breast carcinoma in the appropriate clinical context. GATA-3 reactivity in around 70% of triple-negative breast carcinomas is also clinically useful. Significant reactivity in gynecologic squamous cell carcinomas suggests that GATA-3 alone cannot reliably distinguish these tumors from urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 19 publications
7
62
0
3
Order By: Relevance
“…At the same time, ER-α is engaged in a positive cross-regulatory loop with GATA-3 as it also directly stimulates the transcription factor GATA-3, indicating that GATA-3 in association with ER can regulate critical genes in hormone-responsive breast cancer with statistically significant correlation between GATA-3 and ER expression [4,7,13,14]. GATA-3 has been developed as an immunohistochemical marker for breast and urothelial carcinomas for use in routine diagnostic pathology practice [8,15]. Although breast cancer is common, MAM and GCDFP-15 lack the desired sensitivity while ER and PR serve as prognostic markers with only adjunctive diagnostic utility, especially in the setting of a high-grade triple negative metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, ER-α is engaged in a positive cross-regulatory loop with GATA-3 as it also directly stimulates the transcription factor GATA-3, indicating that GATA-3 in association with ER can regulate critical genes in hormone-responsive breast cancer with statistically significant correlation between GATA-3 and ER expression [4,7,13,14]. GATA-3 has been developed as an immunohistochemical marker for breast and urothelial carcinomas for use in routine diagnostic pathology practice [8,15]. Although breast cancer is common, MAM and GCDFP-15 lack the desired sensitivity while ER and PR serve as prognostic markers with only adjunctive diagnostic utility, especially in the setting of a high-grade triple negative metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that GATA-3 sensitivity in ER negative breast cancer cases to be 62.5 % compared to 42.8 % and 50 % for MAM and GCDFP-15 respectively; however, this needs to be interpreted cautiously due to the small number of ER negative cases in our cohort. The challenge with GATA-3 is its lack of tissue specificity as it can be expressed in urothelial carcinomas, pulmonary carcinomas, mesotheliomas, salivary gland tumors, and all skin adnexal tumors [5,6,8,15,17]. In the right morphologic and clinical setting GATA-3 has proven to be a useful marker in distinguishing breast cancer from other non-mammary carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care must be taken in evaluating the teratoma data, however. Many human tumors express CGB (53)(54)(55), and some secrete placental CG and CSH1 (56), whereas others, including aggressive breast carcinomas, contain areas that are both GATA3 + and KRT7 + (57). Because the areas of teratomas expressing trophoblast markers were sporadic and not well characterized histologically, the proof that they represent fetal placenta remains weak.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither CD10 nor calretinin is highly sensitive or specific for mesonephric differentiation, and GATA3 staining has great variability in both intensity and extent. In addition, weak reactivity of GATA3 has been observed in 7% of endometrial carcinomas [16]. Therefore, at this time, there are no antibodies that distinguish MA from Müllerian carcinomas.…”
Section: Discussionmentioning
confidence: 85%